Liturgical categories and ritual process. The Nordic welfare states encounter with workplace health problems - Hem, Hans-Einar (AM. Rivista della Società Italiana di Antropologia Medica, 2001)
Liturgical categories and ritual process. The Nordic welfare states encounter with workplace health problems